2017
DOI: 10.1088/1361-6528/aa7cad
|View full text |Cite
|
Sign up to set email alerts
|

Efficient room temperature hydrogen sensor based on UV-activated ZnO nano-network

Abstract: Room temperature hydrogen sensors were fabricated from Au embedded ZnO nano-networks using a 30 mW GaN ultraviolet LED. The Au-decorated ZnO nano-networks were deposited on a SiO/Si substrate by a chemical vapour deposition process. X-ray diffraction (XRD) spectrum analysis revealed a hexagonal wurtzite structure of ZnO and presence of Au. The ZnO nanoparticles were interconnected, forming nano-network structures. Au nanoparticles were uniformly distributed on ZnO surfaces, as confirmed by FESEM imaging. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…That is, the LoD under light with a 9 V bias was calculated at 3.5 ppm, which is much lower when compared with 3 and 6 V bias conditions (see the Supporting Information, Table S1). The results obtained at near RT are impressive, given that previous studies have successfully reached an LoD of <10 ppm with good selectivity and sensitivity toward H 2 gas, however at temperatures above 100 °C. , In other studies where the LoD has been reported below 10 ppm at RT, there have been challenges or no reports in terms of selectivity of the sensor toward H 2 gas. Findings suggest that the sensor response magnitude in the presence of light with a 9 V bias was better and has less baseline noise and better signal-to-noise ratio (SNR = 72), which also results in better detection limit when compared to the SNR at a similar sensing condition in the absence of light [SNR = 0.006, see Table S1 (Supporting Information)]. The increase in the baseline noise in the absence of light at 9 V bias was attributed to the reduced number of charge carries as portrayed in an earlier analysis. , Both response ( t 90‑res ) and recovery ( t 90‑rec ) times were calculated for the sensor under the conditions of 500 ppm H 2 , from 3 to 9 V bias, under light illumination, at 33 °C, whose results are presented in Table S2.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…That is, the LoD under light with a 9 V bias was calculated at 3.5 ppm, which is much lower when compared with 3 and 6 V bias conditions (see the Supporting Information, Table S1). The results obtained at near RT are impressive, given that previous studies have successfully reached an LoD of <10 ppm with good selectivity and sensitivity toward H 2 gas, however at temperatures above 100 °C. , In other studies where the LoD has been reported below 10 ppm at RT, there have been challenges or no reports in terms of selectivity of the sensor toward H 2 gas. Findings suggest that the sensor response magnitude in the presence of light with a 9 V bias was better and has less baseline noise and better signal-to-noise ratio (SNR = 72), which also results in better detection limit when compared to the SNR at a similar sensing condition in the absence of light [SNR = 0.006, see Table S1 (Supporting Information)]. The increase in the baseline noise in the absence of light at 9 V bias was attributed to the reduced number of charge carries as portrayed in an earlier analysis. , Both response ( t 90‑res ) and recovery ( t 90‑rec ) times were calculated for the sensor under the conditions of 500 ppm H 2 , from 3 to 9 V bias, under light illumination, at 33 °C, whose results are presented in Table S2.…”
Section: Resultsmentioning
confidence: 81%
“…These relate to their irreproducibility, nonselectivity, and high operating temperatures required for low analyte concentration analysis. 13 Working at low temperatures (140 °C) usually reduces any catalytic activity of the sensitive layer toward the gaseous analyte, 53 partly because of the difficulty (i.e., lack of energy) in overcoming the activation energy or the excitation of electrons to initiate the reaction; thus, another method to effectively enhance the reaction rate while maintaining low operating temperatures needs to be employed. Optical excitation of metal oxide semiconductor-based catalysts may enhance the oxygen (second reactant) sorption capacity on the surface through the separation of electron and hole pairs, resulting in the excitation of the electron to the conduction band, thus providing a higher number of electrons on the surface to participate in the reaction.…”
mentioning
confidence: 99%
“…The results show that the responses of the gas sensors are stable. During operating temperature at 100 °C, electron concentration for the sensing reaction increases due to the sufficient thermal energy at higher temperature to overcome the potential barrier [ 25 ]. Introducing the 365-nm UV light has significantly improved the sensing stability of CuO NW sensor at the initial stage of sensing cycle.…”
Section: Resultsmentioning
confidence: 99%
“…Synergic interaction between noble metal catalyst and photo-UV illumination has been explored to improve the sensor sensitivity. Kumar and co-workers achieved RT sensor performances from Au-modified ZnO networks to hydrogen under UV illumination [ 48 ]. The sensor exhibited a response of ~ 21.5% to 5 ppm hydrogen, while no response was recorded without UV illumination.…”
Section: Photoactivated Metal Oxide Semiconductorsmentioning
confidence: 99%